Unveiling the Gender Paradox Dynamics of Power, Sexuality and Property in Kerala - N.B., Lekha; Palackal, Antony (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Both nationally and internationally, the south Indian state of Kerala has been an object of study for its matrilineal kinship organization among some communities, as well as its achievements in education, literacy, and life expectancy for women against a weak economic base. Nonetheless, scholars have drawn attention to a paradox in Kerala's model of development, namely women's deteriorating social position in Kerala and the rise in violence against women. Against this backdrop, this book explores the intersections of gender, sexuality, marriage, family and kinship as related to the matrilineal Nayar community in Kerala. Chapters unravel the interplay between the triple categories of gender, power and social development as they play out at the micro, meso, and macro levels of society, probing the ways in which Nayar women practice agency. Ultimately, the authors explore how the strength of the Nayar community can be used as a case study toward circumventing the prevailing gender paradox and re-imagine a more liberated, empowered and self-reliant woman not only in Kerala, but in India at large. This book will be of interest to scholars in sociology, cultural studies, gender studies, and development studies, particularly those with a focus on South Asia.
Chapter 1: Introduction -- Chapter 2: Gender within Matriliny -- Chapter 3: Women, Sexuality and property Rights -- Chapter 4: Making of Culture in a Caste Matrix -- Chapter 5: Female Authority Intersecting Ideology and Identity -- Chapter 6: Property Matters -- Chapter 7: Changing Gender Relations -- Chapter 8: Conclusion.
Keywords: Sex; Sociology; Social groups; Social structure; Equality; Property; Common law; Gender Studies; Sexuality Studies; Sociology of Family, Youth and Aging; Social Structure; Common Property and Land Law